2002
DOI: 10.1016/s0008-6363(02)00505-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptor subtypes and neuronal nitric oxide synthase in neutrophils from women and men Regulation by estrogen

Abstract: Although the in vivo levels of circulating estrogen concentrations seem to be associated with overexpression of both ERalpha and ERbeta in neutrophils from premenopausal women, which was further confirmed by the in vitro experiments with neutrophils from women, in vitro incubation of neutrophils from men with 17beta-estradiol only increased ERalpha protein expression which was associated with enhanced expression of nNOS protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 43 publications
4
54
1
1
Order By: Relevance
“…Treatment of either humans or mice with E2 increases numbers of neutrophils in the blood and lungs, respectively (50,51). Neutrophils possess both ER␣ and ER␤ (52,53). Functionally, in vitro exposure of neutrophils to E2 (i) increases degranulation, elastase release, and production of reactive oxygen species, (ii) inhibits caspase 3/9 and delays apoptosis, and (iii) increases cell adhesion molecules and interactions with endothelial cells (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of either humans or mice with E2 increases numbers of neutrophils in the blood and lungs, respectively (50,51). Neutrophils possess both ER␣ and ER␤ (52,53). Functionally, in vitro exposure of neutrophils to E2 (i) increases degranulation, elastase release, and production of reactive oxygen species, (ii) inhibits caspase 3/9 and delays apoptosis, and (iii) increases cell adhesion molecules and interactions with endothelial cells (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are recruited into the tissue by local production of cytokines and then contribute to tissue destruction by the production of reactive oxygen metabolites, granule enzymes, and cytokines that further amplify the inflammatory response by acting on macrophages and lymphocytes (Kadl and Leitinger, 2005). Neutrophils were shown to express GR and ER receptor, suggesting a potential role of these receptors in the regulation of neutrophil function (Molero et al, 2002). Other studies have also demonstrated that GR may modulate leukocyte-endothelial cell interactions during inflammation through regulation of endothelial adhesion molecules (Schramm and Thorlacius, 2004).…”
Section: Cross-talk Between Gr and Er In A Model Of Inflammation 139mentioning
confidence: 99%
“…The effects of E 2 , PPT, and DPN on estrogen-mediated immunomodulation were investigated in ovariectomized (ovx) mice, PPT but not DPN showed effects on thymus (Li & McMurray 2006). Both ER subtypes have been found in different leukocyte populations in human tissues and in peripheral blood (Stygar et al 2001, 2006, Molero et al 2002. Still, the functional activity and importance of ERs in blood cells are principally unknown.…”
Section: Introductionmentioning
confidence: 99%